Administration of Collagen Peptide Prevents the Progression of Pulmonary Fibrosis in Bleomycin-Treated Mice - Minami Yoshihara; Chisaki Asatsuma; Ayuna Masuko; Keiya Iwaasa; Yuki Saito-Matsuzawa; Hideyuki Sone; Shin Kamiyama (Biologics, 2023)
Collagen peptides (CPs) are food-derived peptides that possess a variety of bioactive properties. Our study investigates the effects of CP on pulmonary fibrosis in bleomycin (BLM)-treated mice. C57BL/6J mice were subcutaneously injected with BLM for two weeks followed by a three-week experimental diet containing 25 mg/g of CP derived from chicken feet. Supplementation with CP suppressed the increase in lung weight and disruption of lung architecture observed in mice treated with BLM. BLM-treated mice also exhibited higher hydroxyproline content and increased expression levels of type I and III collagen subunit genes in the lungs. CP supplementation exerted no effect on these collagen-related factors; however, it significantly suppressed the gene expression of fibronectin and inflammation-related molecules in the lungs of BLM-treated mice. These findings suggest that CP administration prevents the development of pulmonary fibrosis by acting as an anti-inflammatory agent.